2023
DOI: 10.1101/2023.11.23.568045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection and spread of high pathogenicity avian influenza virus H5N1 in the Antarctic Region

Ashley Bennison,
Alexander M. P. Byrne,
Scott M. Reid
et al.

Abstract: The Antarctic is the only major geographical region in which high pathogenicity avian influenza virus (HPAIV) has never previously been detected. The current panzootic of H5N1 HPAIV has decimated wild bird populations across Europe, North America and South America. Here we report on the emergence of clade 2.3.4.4b H5N1 HPAIV in the Antarctic and sub-Antarctic regions of South Georgia and the Falkland Islands respectively. We initially detected H5N1 HPAIV in samples collected from brown skuas at Bird Island, So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 95 publications
(166 reference statements)
2
26
0
Order By: Relevance
“…Satellite tracks and flipper tagging data confirm the connection between these sites (Campagna et al, 2020;Lewis et al, 2006). Evidence so far indicates that the virus reached South Georgia Island (Bennison et al, 2023).…”
supporting
confidence: 52%
“…Satellite tracks and flipper tagging data confirm the connection between these sites (Campagna et al, 2020;Lewis et al, 2006). Evidence so far indicates that the virus reached South Georgia Island (Bennison et al, 2023).…”
supporting
confidence: 52%
“…This is in contrast to the seabird breeding season 2023/24. In October 2023 the first confirmed H5N1 cases were detected on the Falkland (Malvinas) Islands, and in November on South Georgia Island in the sub-Antarctic 10,12 (Figure 1). Given the overlap of species breeding and migrating via the Falkland Island and South Georgia towards the Antarctic Peninsula and its offshore Islands (e.g., the South Shetland Islands), researchers in the region and the tourist industry have been very diligent in identifying unusual bird behaviour and mortality events.…”
Section: Main Textmentioning
confidence: 99%
“…are known scavengers (Figure 2), leading to high risks of exposure to HPAIV via the consumption of infected carcasses. It is thus no surprise that Brown skuas where often among the first confirmed cases both on South Georgia and the Antarctic Peninsula 10 . This species, which can be observed at shorelines of South America, the Falkland Islands and South Georgia 13 , is likely to be an important player in spreading the virus.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…They all belong to the B3.2 genotype, a reassortant of the original Eurasian A(H5N1) virus introduced into North America in late 2021, and local North American avian influenza viruses (FluGlobalNet, online). Bennison et al (2023) outlined that discrete trait analysis based upon the country of origin suggested that the source of HPAI virus for both South Georgia and the Falkland Islands was Chile. In Asia, Cambodia reported outbreaks of HPAI A(H5N1) to WOAH from a region where human cases of A(H5N1) belonging to clade 2.3.2.1c have occurred (KhmerTimes, online).…”
Section: Hpai Virus Detections In Birds Outside Europementioning
confidence: 99%